Alertness and perception gamification in education toward increase student focus / Muhammad Izzat Adnan - Adnan, Muhammad Izzat (2019)
Recently, learners were digital natives. They grew up with modern technologies. Therefore, teachers had to solve important issues related to the adaptation of the learning process towards students who had different learning styles and new requirements for teaching and learning. Gamification was one of the educational approaches and techniques that can be use to increase motivation and engagement of learners. The aim of the current project was to identify type of gaming component, criteria and guidelines also to develop games for alertness and perception. Lastly to evaluate result of usability from the games. The methodology that has been are GAMED. The significant of the project are to gain the interest of students to learn by playing games and increases their motivation. The testing has been done to student and the result was 30 respondents agree that the games can help improved their focus. For future works, The improvements that could be done in the future is to add more creativity games, for example, adding animations on the screen.